Ayurvedic Management of Gridhrasi w.s.r. to Sciatica - A Case Study (AYUSHDHARA, 2021)
Low back pain is one of the most common diseases affecting 70% to 80% of population. Low back pain affects the people of all ages from children to elder one. Among various causes of low back pain Sciatica is most appearing one. Sciatica is a condition in which pain radiating along the sciatica nerve, which runs down one or both legs from the lower back. Sciatica pain sometimes hampers the person daily activities because of its intensity. As per Ayurvedic classics its features closely resembles the Gridhrasi. In Gridhrasi pain starts from Sphik (hip) and runs down to Kati Prusta (back), Uru (thigh), Jaanu (knee), Jangha (calf), and Pada (foot) along with pain it may be associated with stiffness, heaviness based on Dosha involvement. Contemporary medicine has limitation with short term pain relief or surgical interventions which are sometime more costly to afford and also long term pain medication will have side effects. Ayurvedic treatment has good scope in managing Gridhrasi with Panchakarma procedures with oral medication. Here in this case study Patient was suffering from low back pain radiating to right lower limb she was treated with one course of Katibasti followed by Sarvanga basphasweda with one course of Yogabasti with oral medication. After treatment patient showed remarkable improvement in symptoms, shows improvement of Oswestry Disability score from 68.88% to 22.22% that is moderate disability and would do all routine daily activities properly.